Analysis of Students’ Multiple representation-based Problem - solving Skills - Army Al Islami Ali Putra; Nonoh Siti Aminah; Ahmad Marzuki (Universitas Negeri Makassar, 2020)
This study aims to analyze the profile of students’ problem - solving skills based on multiple representation in senior high school. Problem - solving skills in solving multiple representation are very important in learning Physics. The subjects of this study were 101 students of class XII MAN 1 Ngawi. The method used in this research was quantitative descriptive method. Indicators of the problem - solving abilities that were used included approaches, visuals, applications, and procedures. The types of representation in this research instrument were verbal, figures, graphic and mathematic. The results showed that the problem - solving skills related to the indicator of approach with the form of multiple representation questions got percentages of 36% (verbal), 42% (figural), 24% (graphical), and 43% (mathematical). The visual indicators showed the percentages of 44, 29, 38, and 0 for verbal, figural, graphical, and mathematical respectively. Then the indicators of procedures obtained 36% for the verbal, 30% for the figures, 35% for the graphics, and 0% for the mathematics. Thus, it can be concluded that problem - solving skills possessed by students are different in terms of the percentage each indicator got in the multiple representation test.